2001
DOI: 10.1359/jbmr.2001.16.4.671
|View full text |Cite
|
Sign up to set email alerts
|

Low-Intensity Pulsed Ultrasound Accelerates Rat Femoral Fracture Healing by Acting on the Various Cellular Reactions in the Fracture Callus

Abstract: Low-intensity pulsed ultrasound (LIPUS) has been shown to accelerate fracture healing in both animal models and clinical trials, but the mechanism of action remains unclear. In fracture healing, various consecutive cellular reactions occurred until repair. We investigated whether the advanced effects of LIPUS depended on the duration and timing of LIPUS treatment in a rat closed femoral fracture model to determine the target of LIPUS in the healing process. Sixty-nine Long-Evans male rats that have bilateral c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
216
0
13

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 334 publications
(244 citation statements)
references
References 37 publications
15
216
0
13
Order By: Relevance
“…(Osaka) as previously described (46). Femur specimens were evaluated at the midportion and at 10 mm from the distal end by cross-sectional analysis.…”
Section: Microcomputed Tomographymentioning
confidence: 99%
“…(Osaka) as previously described (46). Femur specimens were evaluated at the midportion and at 10 mm from the distal end by cross-sectional analysis.…”
Section: Microcomputed Tomographymentioning
confidence: 99%
“…Confining the anabolic response to weightbearing bones excludes skeletons incapable of bearing weight (e.g., patients with spinal injuries or muscular dystrophy) or clinically important sites not associated with weight bearing (e.g., distal radius). Considering that electric fields, 24,25 intramedullary pressure, 26 and ultrasound 27,28 can all effectively promote bone formation and fracture healing, the direct application of matrix deformations may not be a required component for WBV to be efficacious.…”
Section: Introductionmentioning
confidence: 99%
“…These results determined that LIPUS have a significant effect on the earlier inflammatory or accelerate to callus formation phases of healing. [22,31,[73][74][75] In a study with a rat femoral fracture model, hard callus area, bone mineral content, mechanical torsion properties were measured at 4 different periods (1-8 days, 9-16 days, 17-24 days, 1-24 days) after expose to LIPUS, along with histologic analysis. The findings reported statistically significant increases in all measured parameters in all groups when compared with the control group.…”
Section: Time-dependent Effectmentioning
confidence: 99%
“…They suggested that LIPUS acts on some cellular reactions at each stage of the fracture healing process. [73] Azuma et al (2001) in an experimental study measured mechanical and histological changes at different time periods during the healing process. They investigated the timing or duration of stimulation effect after 8 and 25 days of LIPUS treatment.…”
Section: Time-dependent Effectmentioning
confidence: 99%